The Urgency of Strengthening Islamic Diversity and Legal Morality in Building Civil Society in the Era of Digital Transformation - Resza Andreas (RESPONSIVE LAW JOURNAL, 2024)
The idea of civil society was first put forward by the philosopher Cicero. Civil society is portrayed as a society that puts forward existing and morals. The discussion of civil society cannot be separated from the era of digital transformation characterized by the use of technology in daily life. The focus of this article is to analyze the strengthening of Islamic diversity and legal morality in building civil society in the era of digital transformation. The method used to find results and discussion is a conceptual approach, which provides a point of view of problem solving analysis seen from aspects of legal concepts behind it, or from the values contained in the discussion. The results showed that to build a civil society is necessary to strengthen the value of Islamic religious values, which also contains the moral values necessary to build a law that is advanced, realize the principles of democracy, and guide the behavior of society in the era of digital transformation to achieve civil society that is already in sight.